Parting the Curtain: The Virgin Heroine and the ‘Westoxified’ Villain in Contemporary Iranian Romance Novels - Elham Naeej (Journal of Popular Romance Studies, 2021)
This paper explores the concept of virginity in eight popular romance novels published in contemporary Iran and argues that virginity is not only a prerequisite for the heroine, but also the capital with which she can bargain in the novel’s patriarchal world. As a commodity, virginity is interconnected to the ideology of the state – which is often reproduced in the novels – leading to the construction of two distinct versions of femininity. While hegemonic femininity does virginity properly, pariah femininity is connected to the otherized non-virgin. Thus, the romance heroines are forced to grapple with the ingrained virgin / whore complex which permeates these novels and links them inextricably to the rhetoric of Westoxification by painting the West(oxified) non-virgin as a threat to the social order. This obsession with virginity reproduces a number of tropes, among which are forced marriage, child marriage, post-virginity dysphoria and abjection/romanticization of death. The women characters’ ability to perform virginity delineates their fates in the narrative, leading to the stigmatization and damnation of the Westoxified villain and the veneration and martyrdom of the virginal heroine in the battle of incongruous ideologies and discourses around women’s bodies in contemporary Iran.